Increases in Plasma Tryptophan Are Inversely Associated with Incident Cardiovascular Disease in the Prevención con Dieta Mediterránea (PREDIMED) Study. Issue 3 (8th February 2017) - Yu, Edward; Ruiz-Canela, Miguel; Guasch-Ferré, Marta; Zheng, Yan; Toledo, Estefania; Clish, Clary B; Salas-Salvadó, Jordi; Liang, Liming; Wang, Dong D; Corella, Dolores; Fitó, Montse; Gómez-Gracia, Enrique; et al.
Abstract: Background: During development of cardiovascular disease (CVD), interferon-γ–mediated inflammation accelerates degradation of tryptophan into downstream metabolites. A Mediterranean diet (MedDiet) consisting of a high intake of extra-virgin olive oil (EVOO), nuts, fruits, vegetables, and cereals has been demonstrated to lower the risk of CVD. The longitudinal relation between tryptophan and its downstream metabolites and CVD in the context of a MedDiet is unstudied. Objective: We sought to investigate the relation between metabolites in the tryptophan-kynurenine pathway and CVD in the context of a MedDiet pattern. Methods: We used a case-cohort design nested in the Prevención con Dieta Mediterránea randomized controlled trial. There were 231 CVD cases (stroke, myocardial infarction, cardiovascular death) among 985 participants over a median of 4.7 y of follow-up [mean ± SD age: 67.6 ± 6.1 y; 53.7% women; mean ± SD body mass index (in kg/m 2 ): 29.7 ± 3.7]. We assessed plasma tryptophan, kynurenine, kynurenic acid, 3-hydroxyanthranilic acid, and quinolinic acid concentrations at baseline and after 1 y of intervention with a MedDiet. We combined these metabolites in a kynurenine risk score (KRS) by weighting each metabolite by the adjusted coefficient of its associations with CVD. Cox models were used in the primary analysis. Results: Increases in tryptophan after 1 y were associated with a lower risk of composite CVD (HR per SD: 0.79; 95% CI: 0.63, 0.98). The baseline kynurenic acid concentration was associated with a higher risk of myocardial infarction and coronary artery disease death but not stroke. A higher KRS was more strongly associated with CVD in the control group than in the 2 intervention groups ( P -interaction = 0.003). Adjustment for changes in plasma tryptophan attenuated the inverse association between MedDiet+EVOO and CVD. Conclusions: An increase in the plasma tryptophan concentration was significantly associated with a decreased risk of CVD. A MedDiet may counteract the deleterious effects of a high tryptophan risk score.